Pembelajaran Pendidikan Jasmani Adaptif pada Sekolah Luar Biasa selama Masa Pandemi: Studi Analisis - Dimas Duta Putra Utama; Riky Fernando; Lungit Wicaksono (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
After explaining why analytical research studies in adaptive physical education learning during a pandemic are urgently needed, we briefly place the rapidly evolving phenomenon of adaptive physical education learning within the broader aspects of the learning process where content and language have been considered and compare research results with those of other people. people from other educational phases. An in-depth analytical study in an extraordinary school depicting adaptive physical education learning in a time of pandemic. We describe an analytical study that has estimated teacher and student beliefs before attempting to synthesize evidence on whether adaptive physical education learning during a pandemic is beneficial for developing abilities of students with special needs in special schools. We conclude that key stakeholders have serious concerns regarding adaptive physical education learning. The role of teachers and parents is very decisive in the growth and development of children with special needs. In this pandemic period, physical education teachers have higher challenges related to learning in special schools, because the learning of students with special needs is very different from normal students in general.